INOVASI LAYANAN KESEHATAN MENTAL BERBASIS WEBSITE PADA POSYANDU REMAJA: MENTABOOST - Aditya Pratama Rosadi; Cindy Kartikasari Azzahra; Muchammad Rif'at Agiast; Salsabilla Putri Heryawan; Silvia As-syifa Cahyani (Politeknik STIA LAN Bandung, 2023)
This study aims to investigate the impact of social media on adolescent mental health using a quantitative approach. A questionnaire was distributed to a sample of adolescents who actively use social media to collect data on social media usage andlevels of depression, anxiety, and suicidal ideation among adolescents. The results of the study showed that excessive social media use is positively correlated with increased levels of depression and anxiety among adolescents. Furthermore, there is arelationship between cyberbullying and suicidal ideation. The Fear of Missing Out (FOMO) factor also significantly contributes to the negative effects on adolescent mental health. These findings highlight the importance of awareness regarding the risks of excessive social media use and its implications for adolescent mental health. Efforts are needed to promote healthy social media usage and combat cyberbullying. Healthy coping strategies and the development of interpersonal skills can help reduce levels ofdepression and anxiety and promote positive well-being among adolescents.